Open Surgery in the Era of Minimally Invasive Surgery: Pyeloplasty via A Mini Flank Incision in the Treatment of Infants with Ureteropelvic Junction Obstruction - Liu, Xiaodong; Wang, Xinghuan (Urology Journal, 2020)
Purpose: To evaluate the clinical effects of open pyeloplasty via a mini flank incision in the treatment of infants with ureteropelvic junction obstruction (UPJO). Materials and Methods: We retrospectively analyzed 85 cases of infants with UPJO in our hospital from Jan. 2015 to Jan. 2018. The cases were divided into two groups according to the procedure: open pyeloplasty (n=45) and laparoscopic pyeloplasty (n=40). After 12 24 months of follow-up, the clinical effects of the two groups were compared. Results: There was no significant difference in age between the two groups (P = .1). The operation time, postoperative fasting time and the indwelling time of the perirenal drainage tube in the open group were shorter than those in the laparoscopic group (68.0 ± 15.3 minutes versus 79.6 ± 18.8, P = .002; 5 ± 1 hours versus 14 ± 8.2 hours, P =.001; 2.8 ± 0.8 days versus 3.7 ± 1.3 days, P = .001, respectively), and there was no significant difference in the volume of intraoperative bleeding (2.1±0.9 versus 2.2±0.6, P=.55). The number of recurrences and complications in both groups were 0 versus 2 (P = .22) and 5 versus 7 (P = .40), respectively. Conclusion: Open pyeloplasty via a mini flank incision has the advantages of being minimally invasive, safe, effective, and easy to master, and it requires a short operation time. It is a reasonable option for the treatment of infants with UPJO despite this era of minimally invasive surgery.